Fuzzy logic controller on control boost DC-DC converter: article / Mohd Farez Saleh Udin - Udin, Mohd Farez Saleh Udin (Universiti Teknologi MARA (UiTM), 2009)
This paper describes the design of a Fuzzy Logic Controller using voltage output as feedback for significantly improving the dynamic performance of Boost Dc-Dc Converter by using MATLAB/Simulink software. The objective of this proposed methodology is to develop Fuzzy Logic Controller on control Boost Dc-Dc Converter using MATLAB/Simulink software. Fuzzy Logic Controller has been implemented to the system by developing Fuzzy Logic Controller algorithm. The design and calculation of the components especially for the inductor has been done to ensure the converter operates in Continuous Conduction Mode (CCM). The evaluation of the output has been carried out and compared by software simulation using MATLAB/Simulink software between the open loop and closed loop circuit. Tlie simulation results are shown that voltage output is able to be control in steady state condition for Boost Dc-Dc Converter by using this methodology.